Scenography for Paraíso Zona Norte (Paradise North Side) and other Nelson Rodrigues’ plays (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
J.C. Serroni entered the universe of the Brazilian playwright Nelson Rodrigues since he began his career as a set designer, back in the days of TV Cultura's teletheaters. With the famous director Antunes Filho, Serroni worked as set designer in several of Rodrigues’ plays, always in constant research of their scenic symbols, technical materials and forms of artistic production. Beside Eid Ribeiro and Gabriel Villela, he continued his creative work of studying this universe. In this essay, he recalls the scenographic solutions for the plays Álbum de Família (Family Album), Toda Nudez Será Castigada (All Nudity Shall Be Punished), Beijo no Asfalto (The Deceased Woman), Os Sete Gatinhos (The Seven Kittens) and Vestido de Noiva (Wedding Dress).
Keywords: scenography; Nelson Rodrigues; Paraíso Zona Norte